2016
DOI: 10.1002/gj.2857
|View full text |Cite
|
Sign up to set email alerts
|

Syn‐convergence exhumation of continental crust: evidence from structural and metamorphic analysis of the Monte Cecu area, Alpine Corsica (Northern Corsica, France)

Abstract: In the Corsica Island, a stack of metamorphic continental units derived from the European continental margin is thrust over a pre‐Alpine basement during the convergence‐related processes in the Late Eocene–Early Miocene time span. The Piedigriggio‐Prato Unit is representative of these units. Its tectono‐metamorphic history has been reconstructed by an integrated approach, ranging from map‐ to meso‐ and microscopic scale analyses. This unit is characterized by a polyphase deformation history that consists of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(68 citation statements)
references
References 89 publications
(153 reference statements)
6
62
0
Order By: Relevance
“…Blueschist assemblages in the unit have been described by regional studies (Bezert and Caby, 1988;Malasoma et al, 2006;Molli, 2008;Di Rosa et al, 2016) and are observed in all suitable rock types, such as in metapelites from cover rocks, metabasic dykes, and in some of the granitoid suites from the basement. Peak metamorphism has been initially constrained to 250-350 • C and 0.4-0.55 GPa (Bezert and Caby, 1988) or more recently more closely bracketed at 325-370 • C and 0.75-0.85 GPa (Malasoma et al, 2006;Di Rosa et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…Blueschist assemblages in the unit have been described by regional studies (Bezert and Caby, 1988;Malasoma et al, 2006;Molli, 2008;Di Rosa et al, 2016) and are observed in all suitable rock types, such as in metapelites from cover rocks, metabasic dykes, and in some of the granitoid suites from the basement. Peak metamorphism has been initially constrained to 250-350 • C and 0.4-0.55 GPa (Bezert and Caby, 1988) or more recently more closely bracketed at 325-370 • C and 0.75-0.85 GPa (Malasoma et al, 2006;Di Rosa et al, 2016).…”
Section: Introductionmentioning
confidence: 91%
“…1), each of them corresponding to different peak metamorphic con- These occurrences document the progressive underthrusting of these units down to different depths and their insequence contractional exhumation within an Alpine-age, east-dipping subduction system (Mattauer et al, 1981;Bezert and Caby, 1988;Jolivet et al, 1990;Garfagnoli et al, 2009;Molli and Malavieille, 2011;Maggi et al, 2012;Di Rosa et al, 2016;Guyedan et al, 2017;Beaudoin et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations